Cochrane Database of Systematic Reviews 2012
DOI: 10.1002/14651858.cd003577.pub3
|View full text |Cite
|
Sign up to set email alerts
|

Techniques and materials for skin closure in caesarean section

Abstract: There is currently no conclusive evidence about how the skin should be closed after caesarean section. Staples are associated with similar outcomes in terms of wound infection, pain and cosmesis compared with sutures, and these two are the most commonly studied methods for skin closure after caesarean section. If staples are removed on day three, there is an increased incidence of skin separation and the need for reclosure compared with absorbable sutures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
50
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 44 publications
(50 citation statements)
references
References 28 publications
0
50
0
Order By: Relevance
“…Clay et al reported similar rates that favored suture 50/385 (13.0%) vs. 28/492 (5.7%; pooled OR, 2.11; 95% CI 1.29–3.48). The Cochrane review 21 including these same studies concluded that there is “no conclusive evidence about how the skin should be closed after cesarean section.”…”
Section: Discussionmentioning
confidence: 99%
“…Clay et al reported similar rates that favored suture 50/385 (13.0%) vs. 28/492 (5.7%; pooled OR, 2.11; 95% CI 1.29–3.48). The Cochrane review 21 including these same studies concluded that there is “no conclusive evidence about how the skin should be closed after cesarean section.”…”
Section: Discussionmentioning
confidence: 99%
“…3,4 At the end of the operation, the skin incision is typically closed with the placement of either a continuous subcutaneous suture that dissolves over time or multiple metal staples that are removed at a later date. 3,[5][6][7] Our objective was to evaluate whether the wound complication rates after cesarean delivery differ between women whose skin incisions are closed with suture as compared with staples. 3,[5][6][7] Our objective was to evaluate whether the wound complication rates after cesarean delivery differ between women whose skin incisions are closed with suture as compared with staples.…”
mentioning
confidence: 99%
“…1 Although as many as 1.3 million women undergo this surgery annually in the United States, 2 guidance regarding best practices for skin closure is limited. 3 Generally, a cesarean delivery is performed through a suprapubic low transverse skin incision. At the end of the operation, the skin incision is typically closed with the placement of either a continuous absorbable suture or interrupted staples that are removed at a later date.…”
Section: Methodsmentioning
confidence: 99%